DECISION MAKING FACTORS ON FAMILY FARMS: A COMPARISON OF MACEDONIAN AND IRISH FARMS - Radinoska, Elena; Kotevska, Ana (Faculty of Agricultural Sciences and Food- Skopje, 2017)
Family farming is the most common farming model in Europe. However, family farms vary in terms of their size and available resources, as well as the economic, agro-environmental and social contexts they operate in. There are many internal and external factors influencing the decision-making process on family farms, so often this process is based on boundary rationality. The aim of this research is to identify and compare the factors that influence the decision-making process of family farms in two countries with different working environments; Republic of Macedonia and Republic of Ireland. The research is based on observations of the agricultural infrastructure in both the R. Macedonia and the R. Ireland; a survey of family farms in both countries; and lastly informal conversation with the farmers. The implementation of the survey took place in July 2017, with 30 questionnaires in total (15 in each country). The results showed differences in general external factors, whereas specific external factors are more similar in both countries. In terms of internal factors, differences are most often present in the perception farmers have for farming as an occupation that they pass on to future generations.
Keywords: general external factors, internal factors, Republic of Ireland, Republic of Macedonia, specific external factors